The Influence of the Role Playing Method on the Speaking Ability of Lower Grade Elementary School Students in East Jakarta - Treviana, Rizka Millennia Clara; Pranata, Khavisa (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The results of observations of third-grade students at SDS Bina Siswa East Jakarta found that students’ speaking ability tends to be low because of a lack of self-confidence, low understanding, and the inaccuracy of the learning methods used, especially to improve speaking skills. In connection with this problem, appropriate learning methods are needed to improve students’ speaking skills. The use of appropriate learning methods will encourage the creation of meaningful learning and make students actively involved in learning in the future, one of which is the role-playing method. Based on this, this study aimed to determine the effect of the role-playing method on the speaking ability of third-grade students at SDS Bina Siswa East Jakarta. Quantitative research methods with quasi-experimental research types and research design posttest control group design. Data was collected using a performance test to measure students’ speaking ability in the form of a speaking ability assessment sheet and then analyzed by t-test. Based on the calculation of the t-test, a significance value of less than 0.05 is obtained; this proves that there is a difference in the results of the speaking ability performance test between the experimental group and the control group. With these differences, role-playing can affect the speaking ability of class III students at SDS Bina Siswa East Jakarta.